Analyzing the Direct and Indirect Effects of Coping Self-Efficacy on Well-Being via Quality of Life : Coping Self-Efficacy's Impact on Well-Being - Saeed, Shahla; Ahmad, Summiya; Muhammad, Hayat (Pakistan Journal of Health Sciences, 2024)
Understanding the intricate interplay between coping self-efficacy, quality of life, and overall well-being is essential in exploring the factors that contribute to individual resilience and psychological thriving. Objective: To test coping self-efficacy's direct and indirect (through quality of life) effect on well-being. Methods: Using purposive sampling, data were collected from literate adults aged 18 and above in Pakistan. Sample (N=150), mean age=22.65 years consisted of 51 males (34%) and 99 females (66%). Informed consent was taken, and participants filled out the questionnaire consisting of the PERMA profiler, generalized self-efficacy scale, world health organization quality of life brief and demographic sheet. Results: Data analysis showed that coping self-efficacy positively affects well-being (B=3.98, p <0.01). The meditational model showed a significantly positive direct effect (B=.2.78, p >0.01) as well as the indirect effect of coping self-efficacy on well-being (B = 1.20, 95% CI = 0.46, to 1.90). These results show that having higher coping self-efficacy will have an accelerating effect on well-being. Similarly, coping self-efficacy also increases the quality of life, further increasing well-being. Conclusions: An individual’s well-being increases in the presence of higher coping self-efficacy, and this relation is accelerated further in the presence of better quality of life. Thus, the quality of life and self-efficacy can be targeted in intervention programs to enhance well-being for living a more fulfilling life and to create more resilient citizens.